Pengaruh Promosi Tabungan Bank Sumsel Babel Syariah Terhadap Minat Menabung Masyarakat Kota Palembang - Mawardi Mawardi (Al-Tijary, 2018)
This study aims to determine the interest of Palembang’s people to save, especially saving in a sharia-based regional bank, namely Bank Sumsel Babel Syariah. This research was conducted for three months using primary data by distributing questionnaires, books and related journals, the location of the study was in the city of Palembang. the sampling techniques used in this research was random sampling techniques with a total sample of 100 respondents and analyzed with multiple linear regression. The results of this study shown that Advertisements and Publicity have effect on people's saving interest, while sales promotion and personal sales did not affect people's saving interest.